Relationship between physical activity participation and health condition among UiTM Seremban resident students / Nurul Nursyafidah Mahrup - Mahrup, Nurul Nursyafidah (2016)
This present study aimed to investigate four main purposes, which are: (1) to identify the level of physical activity participation among UiTM Seremban resident students; (2) to identify physical health condition among college residents students; (3) to compare the level of physical activity participation between gender; (4 ) to identify the relationship between physical activity participation and health condition among college residents students at UiTM Seremban. A sample of 270 students from both gender aged from 18 to 37 years old completed a set of physical activity questionnaire and their current health condition. The results showed that 48.1 % of students were classified as inactive that indicated that majority were at low level of physical activity. Besides, the result also showed that fifty percent of students are at good condition for their health. Hence, students show that they still can have a good health condition even though they did not actively participate in physical activity. However, there were significant differences in physical activity participation between gender (t =5.7 55, p =.000). Male students showed clearly high participation in physical activity compared to female students. Through the identification of physical activity participation and health condition among the respondents, there is a relationship between physical activity and health. This study also provide useful base for further research in this area of interest.